GO ORGANIK: PELATIHAN PENGOLAHAN PUPUK ORGANIK BERBAHAN DASAR KOTORAN KAMBING UNTUK MENINGKATKAN PRODUKTIVITAS HASIL PERTANIAN DI DESA JERO GUNUNG - Muslim, Edwin; Audil, Rohyatul; Purba, Ridoni Saoloan; Dewi, Astika Sari; Asiyah, Nurani; Atika, Elda Nur’; Jannah, Raudatul; Nurisnaniah, Nurisnaniah; Desa, Wahyu Anggara; Puspitasari, Candra Eka (Jurnal Pepadu, 2024)
The majority of the people of Jero Gunung Village work as farmers and breeders with one of the main problems being the limited availability of fertilizer to fulfill plant nutrition and support agricultural products. Apart from that, from the livestock aspect, people do not utilize the potential of livestock waste. So, activities need to be carried out to explore the potential and socialize this potential to the community, namely by Go-Organic, namely training in making trichocompost organic fertilizer. The aim of this training is to increase the understanding of breeders and farmers in Jero Gunung Village regarding how to make organic fertilizer from livestock manure, especially goats. The method of training activities carried out is in the form of socialization which consists of delivering material by Cooperation Partner experts from CV. Persada Hijau, question and answer session, and practice of making organic fertilizer guided by facilitators, namely PMD KKN students from Jero Gunung Village. The people who attended were enthusiastic about the activity, especially because the results of the activity were trichocompost fertilizer which had been made and then distributed to the people who attended.